Pengembangan Media Pembelajaran Papan Kosakata Untuk Melatih Kemampuan Membaca Permulaan Di Kelas II SDN 18 Ampenan - Magfirah; Siti Istiningsih; Hasnawati (STAI AL-AMIN, 2026)
This study aims to produce vocabulary board media for the early reading skills of second-grade students at SDN 18Ampenan. This research is a type of Research and Development (R&D) using the ADDIE development model. This research uses 5 stages, namely Analysis, Design, Development, Implementation, and Evaluation. The data collection tool used a questionnaire. The results showed that the vocabulary board media developed was highly valid. Based on the assessment by subject matter experts, the criteria for validity were obtained with a percentage of 82%. The assessment by media experts obtained the criteria for high validity with a percentage of 88%. The student response obtained the criteria for high practicality with a percentage of 92.13%.